Factors influencing the behavioral intention to listen to IIUM.FM among non-listeners - Mohamed, Shafizan; Wok, Saodah (AESS Publications, 2020)
This study is part of a longitudinal study done on the audience reception of IIUM.FM, a campus radio the first study or phase 1 was done in 2011 and the second phase was done in 2016. This study specifically compares the non-listeners in Phase 1 (2011) and Phase 2 (2016) in terms of demographic characteristics, academic-related information and computer-related information. In addition, both internal and external factors that may intensify the listening to IIUM.FM are explored and so that the barriers and challenges facing the listeners are eliminated in the near future as IIUM.FM will remain as the only campus radio in IIUM. The same survey questionnaire is used in the data collection at both phases of the study. In addition to the comparison between both phases using t-test and ONEWAY ANOVA, a simple-multiple regression is conducted to determine the predictors of behavioral intention to listen to IIUM.FM. If the predictor is considered a barrier then it should be eliminated so that the listening habit of the students can be improved especially now that the radio can be listened to via multiple sources such as the app, webstream and social media. If the barriers are the reasons that prevent listening to IIUM.FM are removed, then there is a possibility that IIUM.FM are listened by many more students not only among IIUM students but also others worldwide.